Tree lover - Bond, Ruskin (Gurugram: Puffin Books, 2017)
Read on as Rusty tells the story of his grandfather$1 (Bs relationship with the trees around him, who$1 (Bs convinced that they love him back with as much tenderness as he loves them.s
Keywords: Children's stories; Fiction